ANALISIS PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, UKURAN DEWAN KOMISARIS, DAN MEDIA EXPOSURE TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL - Yunus Pakpahan; Lasmanita Rajagukguk (Universitas Kristen Krida Wacana, 2018)
The aim of this study is to analyse the effect of profitability, firm size, commissioner board size, and media exposure to disclosure of corporate social responsibility. The analytical method used is multiple linear regression. The data in this study is a secondary data from financial reports companies listed on the Indonesia Stock Exchange (IDX) from 2014 until 2016, with 151 companies as observation companies and 82 companies as sample. Based on test result analysis, profitability, commissioner board size, and media exposure effect on the disclosure of corporate social responsibility. While firm size has no effect on the disclosure of corporate social responsibility.Keywords : Corporate social responsibility, profitability, firm size, commissioner board size, media exposure.